ANALISIS DETERMINAN KORUPSI DI ERA OTONOMI DAERAH DI INDONESIA (Studi Kasus Provinsi Jawa Tengah) - Friska Yuana Silaen; Hadi Sasana (Universitas Diponegoro, 2013)
In central java become widespread corruption in all sector of the local budget,infrastructure, social assistance and education. This study aimed to analyze the effect of GDP percapita, population of women who work, literacy rates and local taxes to corruption in Central JavaProvince. The data used are secondary data. Secondary data were obtained from the CentralBureau of Statistics and the Commission for the Eradication of Corruption,Collusion andNepotism (KP2KKN) in Central Java Province. The analysis tool used is multiple regression withSPSS 16.0.The results showed that of the four independent variables, only two variables weresignificantly positive effect on the GDP per capita corruption and local taxes, whereas no effectwas the women who work and literacy rates.